Ancient Religions - Assmann, Jan; Attridge, Harold W; Beard, Mary; Beaulieu, Paul-Alain; Bremmer, Jan; Cazanove, Olivier de; Collins, John J; Frankfurter, David; Graf, Fritz; Johnston, Sarah Iles; Lincoln, Bruce; Malandra, William; et al. (Harvard University Press, 2021)
Frontmatter -- Contents -- Introduction -- Note on Translation and Transliteration -- Abbreviations -- Maps -- Encountering ancient religions -- What Is Ancient Mediterranean Religion? -- Monotheism and Polytheism -- Ritual -- Myth -- Cosmology: Time and History -- Pollution, Sin, Atonement, Salvation -- Law and Ethics -- Mysteries -- Religions in Contact -- Writing and Religion -- Magic -- Histories -- Egypt -- Mesopotamia -- Syria and Canaan -- Israel -- Anatolia: Hittites -- Iran -- Minoan and Mycenaean Civilizations -- Greece -- Etruria -- Rome -- Early Christianity -- Epilogue -- Contributors -- Index